(untitled) (Eurasian Research Bulletin, 2022)
In modern society, innovation technologies expand to almost every field of human activity, including such wide field as education. Innovation in education is a highly contentious issue. Education is sometimes perceived as one of the most conservative social systems and public policy fields.